The Challenges of Diversion at LKS Ummu Syahidah Gorontalo For Juvenile Offenders - Maku, Dwi Citra Maharani; Ekawaty Ismail, Dian; Apripari, Apripari (Estudiante Law Journal, 2024)
The purpose of this research is to determine the implementation of diversion efforts against children who commit crimes at LKS Ummu Syahidah Gorontalo. The research method used in this research is an empirical research method using a qualitative approach. The results of this research are that the application of diversion in resolving criminal acts of abuse committed by children at LKS Ummu Syahidah Gorontalo is not yet optimal because from 2021 to 2023 there are only nine criminal acts that meet the requirements for diversion. One of these criminal acts was abuse committed by L who was under 17 (seventeen) years of age. However, in terms of compliance with procedures and regulations, all stages of diversion at LKS Umm Syahidah Gorontalo are in accordance with applicable laws and regulations by the child perpetrator or family, such as asking for compensation that is too large which the child perpetrator or party cannot afford. family so that the implementation of diversion does not reach a successful agreement.